Description of Chlorogomphus auripennis spec. nov. from Guangdong Province, with new records of Chlorogomphidae from Yunnan Province, China (Odonata: Chlorogomphidae) - Zhang, Hao-Miao; Cai, Qing-Hua (Zootaxa, 2014)
A new chlorogomphid, Chlorogomphus (Orogomphus) auripennis spec. nov. (holotype male; Mt Nankunshan, Longmen County, Guangdong Province, China, 20. V. 2008) is described and illustrated. It is the first species belonging to the subgenus Orogomphus recorded from mainland China. The holotype will be deposited in the Collection of Aquatic Animals, Institute of Hydrobiology, Chinese Academy of Sciences, Wuhan City, Hubei Province, China. Chlorogomphus auratus Martin, 1910 and Chloropetalia selysi (Fraser, 1929) are recoded from Chinese territory for the first time. The total number of Chlorogomphidae in China reaches 20. Description of the hitherto unknown female of Chlorogomphus yokoii Karube, 1995 is provided.